A holonic approach to the integration of automated systems - Silva, José Reinaldo (2010)
During several years building and residential automation was thought as a good test bed for integration methods applied to automated systems. A reason for that is the large response time of these systems and the fact that they assemble a set of very well known sub-systems (HVAC, security, elevators, etc.). Even recent innovations in residential environments are based on components based on solid and scalable technology. On the other hand the degree of integration did not improve as much as expected. In this paper we investigate this problem, first from a practical point of view, that is, based on the design and implementation difficulties that designers and vendors face everyday, and second from a technical and methodological point of view, which means finding a new control architecture that could lead to real flexible and integrated systems. Frame architectures could provide a better and modern approach relying on a heterarchic arrangement of sensors and actuators. Some years ago part of the authors proposed a similar architecture based on a generic element called integron. Now we revisit the same point with a new version of the same element focusing on the arrangement of the whole system and on the information flow instead of just distributing the control. We claim that such approach is more efficient. Also it will better fit the requirements in a heterogeneous environment such as residential automation.